Would You Buy a Honda Made in the United States? The Impact of Production Location on Manufacturing Quality - Lacetera, Nicola; Sydnor, Justin (The Review of Economics and Statistics, 2015)
Are location-specific factors important for understanding firms’ heterogeneities? We examine prices and quality metrics for Japanese cars at wholesale auctions, comparing otherwise identical cars assembled in the United States versus Japan. We find similar values regardless of country of assembly. These results indicate that Japanese automakers in general have successfully transferred their practices to their U.S. transplants and that there is no inherent limitation to high-quality automobile production in the United States. Deeper analysis of patterns for Toyota cars, complemented by historical analysis, suggests that although it is possible to transfer standards, quality convergence can require conscious effort and not just cumulative production.